FDI and Indian Stock Market : An Outlook Ahead - Singh, E. N; Prasain, G. P (Journal of Commerce and Trade, 2008)
This paper provides a comprehensive review of the issues relating to FDI and Indian stock markets in the globalized era. It then tries to analyze the major policy issues arising out of the various concerns. Finally, it puts forward some policy recommendations for attracting FDI in India.